Effect of pretreated oil palm frond in enhancing the ruminal degradability, growth performance and meat quality of goats - Rusli, Nor Dini (2020)
The alternative source of ruminant feed is waste from agricultural byproducts such as oil palm fronds (OPF). With an annual production of 13 million tons and low cost, the OPF is of interest in Malaysia as it is abundant. However, OPF contains high neutral detergent fibre with 20% lignin, which can be major constraints to OPF use as livestock feed. It is in line with poor digestibility of OPF in cattle (400 g/kg DM). Consequently, the energy content of OPF ranges between 4.9 and 5.6 MJ of metabolisable energy (ME)/kg DM. There is a need to treat OPF to improve its nutritional value and digestibility to be used as animal feed. Biological pretreatment with enzyme extract from white rot fungi (WRF) is considered a promising technique because of its preferential degradation of lignin with minimum dry matter loss. To make biological pretreatment more effective, a combination of biological with other pretreatments might be necessary. To date, some physical pretreatments have been developed to upgrade the OPF, which include pressing using traditional sugarcane machine. Physical pretreatment may increase particle size, which allows the increase of rumination duration, chewing activity, and ruminal pH, which could offer a favourable environment for rumen microorganisms to thrive. Therefore, the current study was conducted to assess the effect of physical and biological pretreatments of OPF using enzyme extract from WRF on nutritive value and lignocellulosic composition. The study was also investigated to evaluate the potential of physical and biological pretreatments of OPF in enhancing the in vitro rumen degradability, growth and health performances, as well as meat quality of goats. Five different samples of OPF pretreatments were used in this study. The petiole of OPF was subjected to the physical pretreatment (POPF) by pressing using a conventional sugarcane pressing machine and the OPF, which consisted of petiole, leaflet and rachis were biologically pretreated using an enzyme extract of each Ganoderma lucidum (G. lucidum; BGL) and Lentinula edodes (L. edodes; BLE), respectively. Another two samples were subjected to a combination of physical and biological pretreatments of G. lucidum (CGL) and L. edodes (CLE), respectively. The control was non-treated OPF (FOPF). The results revealed that biological pretreatment with enzyme extract of G. lucidum and L. edodes either alone or combination with physical pretreatment reduced crude fibre and increased crude protein. The BGL, CGL, BLE and CLE reduced crude fibre by 15%, 16.6%, 14% and CLE were increased by 58.4%, 58.8%, 48.5% and 54.85% respectively All pretreatments decreased hemicellulose contents significantly as compared to control, but no significant differences were observed among pretreatments. Similarly, the lignin contents (% DM) of all pretreated OPFs showed a significant decrease as compared with the non-treated OPF, but treatments with BGL (10.00) and CGL (10.00) showed the lowest lignin content of OPF (p<0.05). However the physical, biological and combined pretreatments did not change the cellulose content of the OPF (p<0.05). The reduction of lignin content of OPF may indicate the cellulose and hemicellulose are converted into simple fermentable sugars such as glucose and xylose. Physical and biological pretreatments may help to reduce the crystallinity of the cellulose fibre in the OPF while also reducing the size of the materials. For in vitro study, two fistulated Katjang goats consuming OPF and commercial pellet daily were used as rumen fluid donors. In vitro incubation was carried out at 39°C for 24 hours. Both BGL and CGL showed significantly higher propionate and butyrate concentrations as well as apparent rumen degradable carbohydrate (ARDC) with 6.57mg and 6.54mg, respectively as compared to the FOPF. It appeared that BGL and CGL resulted in higher lignin degradation that increased the in vitro rumen degradability, indicating that rumen microbes' access to cellulose was greatly improved. However, comparing these two white rot fungi, G. lucidum seemed more promising for improving the in vitro rumen degradability. Biological pretreatment with enzyme extract of G. lucidum combined with physical pretreatment improved the nutritional values of OPF by decreasing the lignin contents, consequently improving the ruminal degradability along with high total gas production, high VFA and high ARDC. Thus, the biological pretreatment with enzyme extract of G.lucidum was selected to pretreat the OPF for feeding trial study in goats. Twenty, 5-month old male, cross-bred Boer goats with the average initial body weight 21.8±0.5 kg were assigned to treatments in a completely randomised block design of 120-day feeding trial. Five treatment diets containing 20% of OPF with different OPF pretreatments, 50% Napier grass and 30% goat concentrates were used in this study. The T1 consisted of nontreated OPF, T2 contained physically pretreated OPF, T3 with biological pretreated OPF with enzyme extract from WRF, T4 with OPF undergone combination of physical and biological pretreatments and the control (CD) consisted of the basal diet without OPF. During the feeding trial, feed intake and growth performance of goats were measured. After 120-day of the feeding trial, a digestibility trial was carried out on all goats involving total faecal collection. The animals were then slaughtered for carcass traits and meat quality evaluations. The results showed that the intakes of DM, crude protein (CP) and ash were significantly higher in group T3 and T4. However, all pretreatment methods had no adverse effect on body weight (BW) gain. The digestibility of DM, CP, acid detergent fibre and neutral detergent fibre nd 13%, respectively in T4 group as compared with control group. Haematological profile was improved based on reference value in all groups. Total faecal egg respectively. Besides, hot and cold carcass weights, dressing percentage and meat quality measurements were not affected by the pretreatments. Nevertheless, biological pretreatment of OPF has the potential to promote the accumulation of mono- and polyunsaturated fatty acids in the meat. In conclusion, this study has demonstrated that physical and biological pretreatment of OPF either alone or in combination improved the quality of OPF by decreasing the lignin contents, consequently improving the in vitro ruminal degradability along with high total gas production, high VFA and high ARDC. Biological pretreatment of OPF also increased feed intake and some characteristics, chemical composition and meat quality.